Paediatric point‐of‐care ultrasound in a resource‐limited Melanesian setting: A case series. Issue 1 (20th February 2020) - Henry, Jonathan
Abstract: Point‐of‐care ultrasound (POCUS) is an imaging modality with high potential impact on the practice of paediatric emergency medicine in resource‐limited settings. Aside from the obvious diagnostic utility, it facilitates safe procedural guidance at the bedside and provides haemodynamic information to guide resuscitation of shocked states. This five‐patient paediatric case series illustrates the range of POCUS modalities used while working in emergency medicine at a regional referral hospital in Vanuatu. Cases described include a teenager with meningococcaemia, femoral central line insertion in an infant, ventricular septal defect in an infant, a child with a leg abscess, and a child with rheumatic heart disease.